Effects of Moderate Treadmill Exercise and Fluoxetine on Spatial Memory and Serum BDNF Levels in an Animal Model of Post-traumatic Stress Disorder - Sakineh Shafia; Abbas Ali Vafaei; Ali RashidRy-Pour (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Post-traumatic stress disorder (PTSD) develops after major trauma that is accompanied by certain signs, including pervasive fear memories, anxiety, abnormality in spatial and cognition memory, and decrease in hippocampal brain-derived neurotrophic factor (BDNF). Selective serotonin reuptake inhibitors (SSRIs) are the first-line treatment for PTSD. This study aimed at investigating the effects of moderate treadmill exercise and fluoxetine on spatial memory and serum BDNF levels in rat model of PTSD. Materials and methods: In this experimental study, single prolonged stress (SPS) animal model of PTSD was used. Male and female rats were divided into SPS and control groups (n=10 per group). After that, they were subjected to moderate treadmill running (5 days per week/four weeks) and fluoxetine (10 mg/kg/day). Then, behavioral assessment and BDNF measurement were done. Results: SPS male rats showed reduced spatial memory and hippocampal BDNF. Female rats showed more resistance to SPS than male rats. This may be due to the effects of gonadal hormones. The intervention alleviated the SPS-induced alterations in hippocampal-dependent spatial memory and BDNF serum levels in both male and female rats (P<0.05). Conclusion: Combined exercise and fluoxetine administration are more effective in alleviating behavioral and molecular deficits in PTSD patients.